Adoption of Mobile Payment Systems: An Empirical Analysis of Consumer Intentions using the UTAUT2 Model and PLS-SEM - Kumari, Ankita (Management Journal for Advanced Research, 2025)
Mobile payment systems have emerged as a key driver of financial inclusion in India, particularly in the context of digital transformation and the government’s push toward a cashless economy. This study investigates the determinants influencing consumer adoption of mobile payment systems using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model. A structured questionnaire was administered to 124 respondents in Jharkhand, India, and data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) in SmartPLS. The results reveal that performance expectancy, effort expectancy, facilitating conditions, hedonic motivation, and price value significantly influence behavioral intention to use mobile payments, whereas social influence, trust, and habit were found to be insignificant predictors. Furthermore, behavioral intention showed a positive and significant effect on actual usage behavior. These findings provide empirical support for UTAUT2 in the Indian context and highlight the growing role of perceived value and technological convenience in shaping mobile payment adoption. The study offers theoretical contributions to digital finance literature and practical implications for policymakers, fintech firms, and service providers aiming to enhance mobile payment penetration in emerging economies.